RELATIONSHIP OF FAMILY KNOWLEDGE ABOUT PREVENTION OF DECUBITUS WITH THE EVENT OF DECUBITUS IN PATIENTS TOTAL CARE IN THE NEUROLOGY ROOM OF PARIAMAN HOSPITAL RSUD - Aulia Asman and An Aulingga Asman (JOURNAL SCIENTIFIC OF MANDALIKA (JSM), 2021)
Based on a report from Cipto Jakarta Hospital stated that 15.8% of bed rest patients treated at Cipto Jakarta Hospital had pressure sores. This problem is a serious problem because it increases the cost of treatment and slows down the rehabilitation program for sufferers. The number of patients receiving total care at Dr M Jamil Hospital every year continues to increase. Total care patients have a high risk of developing pressure sores. Prevention of pressure sores can also be done by increasing family knowledge about how to prevent pressure sores. The purpose of this study was to examine the relationship between family knowledge about pressure sores and the incidence of pressure sores in total care patients in the Neurology Room of Pariaman Hospital. Decubitus ulcers are skin damage or death that occurs due to impaired blood flow and irritation that covers the protruding bone. This study used a cross sectional study design with a descriptive survey type of research. The population in the study amounted to 32 people. The sampling technique was accidental sampling, obtained as many as 32 samples. Data were collected using questionnaires and observation. Data processing was carried out univariate and bivariate. The results showed that 53.1% had low knowledge, 53.1% did not experience pressure sores. There is a relationship between family knowledge about prevention of pressure sores and the incidence of pressure sores in total care patients in the Neurology Room of Pariaman Hospital, with p value 0.001 <0.05. The incidence of pressure sores is caused by a lack of family knowledge about how to prevent pressure sores. Make changes to the body position of the family being treated by first consulting the health worker on how to make changes to the body position of the family being treated.